Brochures and Newsletters: WC131, 3/2021 - Telg, Ricky; McLeod-Morin, Ashley (EDIS, 2021)
This publication on brochure and newsletter design is the fifth of a five-part series on document design. This series also covers the document design process, principles of document design, elements of document design, and graphic file formats. Updated from previous version: Telg, Ricky. 2012. “Brochures and Newsletters”. EDIS 2012 (7). https://journals.flvc.org/edis/article/view/119922.